1999
DOI: 10.1007/s004310051056
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effectiveness of dexamethasone in neonatal bacterial meningitis

Abstract: Adjunctive dexamethasone therapy does not improve the outcome of neonatal bacterial meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 13 publications
(14 reference statements)
0
42
0
2
Order By: Relevance
“…The possibility of preventing the progressive formation of ventricular septa and loculations with corticosteroids in PIH was discussed by Schultz and Leeds. 24 Whether immune modulation 8,9,16 during NS might reduce this degree of damage to the brain in such patients remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of preventing the progressive formation of ventricular septa and loculations with corticosteroids in PIH was discussed by Schultz and Leeds. 24 Whether immune modulation 8,9,16 during NS might reduce this degree of damage to the brain in such patients remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concluded that the drug is effective in preventing hearing loss in H. influenzae meningitis and has some beneficial effects on hearing and neurologic sequelae in pneumococcal meningitis when given before or at the time of the first antibiotic dose (11). However, in most of the individual trials, these benefits were either marginal or could not be detected at all (12). Furthermore, H. influenzae meningitis has virtually disappeared in countries that have implemented programs with conjugated vaccines in infants and children (13).…”
Section: Institute For Infectious Diseases University Of Bern Ch-30mentioning
confidence: 99%
“…Cochrane review data supports its use in patients with bacterial meningitis in high-income countries, but results were not found to be beneficial from low-income countries. (Daoud AS et al, 1999). Bacterial immunogenicity, host immunity and response, timing and efficacy of antibiotics and steroids used and susceptibility of organism all account for the consequences in low income countries.…”
Section: Role Of Anti Inflammatory Agentsmentioning
confidence: 99%
“…Steroids are also not advised as adjuvant therapy in patients with congenital or acquired CNS anomalies. (Daoud AS et al, 1999).…”
Section: Role Of Steroids In Meningitismentioning
confidence: 99%